Odpravnina franšizojemalca - Kerčmar, Sebastjan (Podjetje in delo, 2024)
Although not regulated by law, franchise agreements are common in business practice and entered into by parties in accordance with the general principles of the law of obligations. A franchise agreement is a mixed agreement that may contain elements of similar standalone contract types such as licensing, agency, distribution, sales and other agreements. The provisions of the Obligations Code that govern the agency agreement stipulate that the commercial agent is entitled to indemnity upon termination of the contractual relationship under the conditions stipulated by law. In the article, the author discusses the question of whether, given the fact that a franchise agreement may also contain elements of an agency agreement, there is a possibility of analogous application of provisions of the Obligations Code governing the right to indemnity of a commercial agent in franchise relationships. In seeking an answer to this question, the author first presents the regulations in Germany, Austria, the Netherlands, and Italy. Subsequently, the author outlines the positions regarding the potential analogous application of indemnity provisions in franchise relationships in Slovenian legal theory and jurisprudence. Finally, taking into account comparative legal frameworks concerning the issue of analogous application of the indemnity institute in franchise relationships, the author presents his own position on that question.
Keywords: agency agreement; franchise agreement; indemnity; odpravnina; pogodba o franšizingu; pogodba o trgovskem zastopanju